Ageing and Secular Social Involvement: Exploring to Subjective Wellbeing - Rachmah Indawati; Kuntoro Kuntoro; Hari Basuki Notobroto; Mochammad Bagus Qomaruddin (International Journal of Public Health Science (IJPHS), 2016)
Religion and Spirituality can provide a unique perspective on life outcomes. The study to deepen subjective well being by exploring its relationships with religious and spirituality (secular values) and characteristics individu by the graph. Data were obtained from survey. The sample was drawn from the population aged 70 or more years in Surabaya by simple random sampling. The instrument using the Philadelphia geriatric center morale scale (PGCMS) and the self spirituality and religious. Most respondents reported being 'low of religiousity and spirituality’ in their lives. The mean PGCMS score was 7.89. The median PGCMS score was 8, 57.4% (139) score PGCSM above the median and 42.6% (103) score PGCSM under the median. Among elderly who were included the high well being category (PGCSM≥10) was 27.2% and most of elderly 72.7% didn’t have good well being. The elderly people who describe themselves as religious are showed graph constant. The graph of self religious is equal according to characteristic individu (age, men and women, marital status). The elderly who describe themselves as spiritual are likely to report greater or lower perceived well being. Exploring using the graph showed different according to characteristic individu. Elderly who demonstrated subjective well being were more likely to male and not married. Elderly’s perception of spirituality depends on characteristic individuals and experience in which individuals live.